Pengembangan Sumber Daya Manusia dan Perbaikan Etika Kerja Karyawan - Rasyid, Maesyaroh; Wahyudi, Dedi (PT Maju Malaqbi Makkarana, 2024)
In today's globalized and fiercely competitive business landscape, developing human resources (HR) and fostering better work ethics among employees are crucial for organizations to thrive. This means investing in training, education, and career growth to improve employees' skills and knowledge. Effective training not only enhances technical abilities but also soft skills like communication and teamwork. Meanwhile, cultivating strong work ethics, like integrity and responsibility, lays the groundwork for a healthy work environment. Employees with good work ethics tend to be more loyal and productive. This study aims to explore how HR development and improved work ethics impact organizational performance. It will look into strategies companies can use to enhance HR quality and foster an ethical work culture. Ultimately, by understanding and implementing these practices, organizations can better navigate complex business challenges and ensure long-term success.